2009
DOI: 10.1377/hlthaff.28.1.160
|View full text |Cite
|
Sign up to set email alerts
|

A Matter Of Race: Early-Versus Late-Stage Cancer Diagnosis

Abstract: We compared the stage at which cancer is diagnosed and survival rates between African Americans and whites, for thirty-four solid tumors, using the population-based Surveillance Epidemiology and End Results (SEER) database. Whites were diagnosed at earlier stages than African Americans for thirty-one of the thirty-four tumor sites. Whites were significantly more likely than blacks to survive five years for twenty-six tumor sites; no cancer site had significantly superior survival among African Americans. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(91 citation statements)
references
References 16 publications
6
79
1
5
Order By: Relevance
“…Contrariwise the majority of patients in our study are symptomatic (95.8%) and presented with LUTS and features of locally advanced or metastatic disease. Numerous studies have found that black men have a higher stage of disease at presentation and are more likely to die of their prostate cancer than their white counterparts [15][16][17]. Powell [17] evidenced that African Americans have similar pathogenic mechanisms and age at PCa initiation to Caucasians but they have a faster growth rate and/or an earlier transformation to clinically significant PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Contrariwise the majority of patients in our study are symptomatic (95.8%) and presented with LUTS and features of locally advanced or metastatic disease. Numerous studies have found that black men have a higher stage of disease at presentation and are more likely to die of their prostate cancer than their white counterparts [15][16][17]. Powell [17] evidenced that African Americans have similar pathogenic mechanisms and age at PCa initiation to Caucasians but they have a faster growth rate and/or an earlier transformation to clinically significant PCa.…”
Section: Discussionmentioning
confidence: 99%
“…That said, a significant black-white difference in breast cancer stage at diagnosis has been reported almost without exception in US studies to date (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Some studies have found that blackwhite differences are significantly reduced after accounting for screening history (22)(23)(24), while others have not (25,29).…”
Section: Race-ethnicitymentioning
confidence: 99%
“…There are race/ethnicity differences in breast cancer stage at diagnosis (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), with African American women significantly more likely than white women to have a late-stage diagnosis. Insurance status is a significant independent predictor of stage, with women who are uninsured or enrolled in Medicaid less likely to access screening mammography (31,32) and more likely to be diagnosed at later stage (20,21,(33)(34)(35).…”
Section: Introductionmentioning
confidence: 99%
“…Prostate-specific antigen (PSA) testing has led to earlier PCa detection, resulting in an increased number of men being diagnosed and treated, which, in turn, has reduced the proportion of PCa metastasis and disease-specific mortality. Nevertheless, African American (AA) men are known to suffer a substantial and disproportionate PCa burden, with studies showing higher incidence, more-advanced stages at diagnosis, more aggressive tumors, and poorer outcomes than other racial groups [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%